Art of Literature in "Kurdistan Press" Published in Sweden - Ahmed, Nawzad A. (Humanities Journal of University of Zakho, 2018)
The Kurdish press in exile has been neglected. There has not yet been an opportunity to collect everything related to the Kurdish press from its inception and then classify it so that it can be kept in an appropriate center. The Kurdish press in exile, like the press inside the country, includes partisan, public and private press, as well as the press of the professional organizations. The newspapers published in the exile, regardless of their names, did not neglect the publication of articles and literary products but it differed from one newspaper to another. The Kurdistan Press was issued every 15 days, but due to financial problems, it was not always issued as such. This newspaper was published in Stockholm from 1986 to 1992. It was a general newspaper, but most of its subjects were political. The newspaper was issued in Kurdish _ Latin alphabets _ as well as Turkish. The Turkish edition was devoted to the Kurdish issue and the news of the Peshmerga and the Kurdish community abroad. Although there is a partisan tendency in the first pages, but in the pages dedicated to literature, art and culture there was no such a tendency. Based on the study and follow-up of the researcher for this newspaper, it turns out to be one of the most important newspapers among the newspapers issued abroad in view of its widespread interest in the publication of literary subjects. In this research, the poetry and prose art published in the above-mentioned newspaper, highlighted. A series of texts which have been considered an integral part of events and daily life of a nation, its members being persecuted, martyred, imprisoned or deported from their homes in the four parts of Kurdistan, have been published in the newspaper. Therefore, the literature, published in this newspaper, is considered a prison literature, in addition to be a political literature as well as the literature of Peshmergas' heroic operations. To get a closer look at this newspaper, I suggest reprinting all its issues in one volume and publishing many copies of it. My recommendation to the Kurdish department of the universities in Kurdistan is to form a committee to search for all the newspapers, issued abroad, especially the newspapers that were written in Latin alphabet for Northern Kurdish dialect (Kurmanjí), at least to change the alphabets of literary and artistic subjects. For example, there are dozens of interviews, literary texts and articles in Kurdistan Press which can be used as the source of many academic subjects.